Effect of sphingosine kinase modulators on interleukin‐1β release, sphingosine 1‐phosphate receptor 1 expression and experimental autoimmune encephalomyelitis. (20th December 2016) - Barbour, Mark; McNaughton, Melissa; Boomkamp, Stephanie D; MacRitchie, Neil; Jiang, Hui‐Rong; Pyne, Nigel J; Pyne, Susan
Abstract : Background and Purpose: The sphingosine analogue, FTY720 (Gilenya R ), alleviates clinical disease progression in multiple sclerosis. Here, we variously assessed the effects of an azide analogue of ( S )‐FTY720 vinylphosphonate (compound 5; a sphingosine kinase 1 activator), ( R )‐FTY720 methyl ether (ROMe, a sphingosine kinase 2 inhibitor) and RB‐020 (a sphingosine kinase 1 inhibitor and sphingosine kinase 2 substrate) on IL‐1β formation, sphingosine 1‐phosphate levels and expression of S1P1 receptors. We also assessed the effect of compound 5 and ROMe in an experimental autoimmune encephalomyelitis (EAE) model in mice. Experimental Approach: We measured IL‐1β formation by macrophages, sphingosine 1‐phosphate levels and expression levels of S1P1 receptors in vitro and clinical score in mice with EAE and the extent of inflammatory cell infiltration into the spinal cord in vivo . Key Results: Treatment of differentiated U937 macrophages with compound 5, RB‐020 or sphingosine (but not ROMe) enhanced IL‐1β release. These data suggest that these compounds might be pro‐inflammatory in vitro . However, compound 5 or ROMe reduced disease progression and infiltration of inflammatory cells into the spinal cord in EAE, and ROMe induced a reduction in CD4 + and CD8 + T‐cell levels in the blood (lymphopenia). Indeed, ROMe induced a marked decrease in expression of cell surface S1P1 receptors in vitro . Conclusion and Implications: This is the first demonstration that an activator of sphingosine kinase 1 (compound 5) and an inhibitor of sphingosine kinase 2 (ROMe, which also reduces cell surface S1P1 receptor expression) have an anti‐inflammatory action in EAE.